The Effect of Professional Education, Experience and Independence on the Ability of Internal Auditors in Detecting Fraud in the Pharmaceutical Industry Company in Central Jakarta - Hamilah, Hamilah; Denny, Denny; Handayani, Evi (International Journal of Economics and Financial Issues, 2019)
This research focuses on the problem that is suspected to have an important influence, namely the ability to detect fraud ( fraud ), from professionalism, experience, independence, and professionalism, the size of the research is internal audit working in pharmaceutical industry companies in Jadebotabek.The population in this study is the enterprise of pharmaceutical industry in Central Jakarta which amounted to 20. Sampling technique used is purposive sampling with sample size 20 companies which produce 100 respondents. The research model used is descriptive method using the classic assumption test, multiple regression analysis, multiple correlation analysis, determination analysis, while testing uses the t-statistical hypothesis test to test partial influence and F-statistics to test the simultaneous effect with a significance level of 5%. Based on the four classical tests, the normality test, the multicollinearity test, the autocorrelation test and the heteroscedasticity test, no variables were found that deviate from the classical assumptions. For testers of this study using the SPSS application version 25.0. The results of the study stated that professionalism had a significant effect on the ability to detect fraud; audit experience has a significant effect on the ability to detect fraud; audit independence has a significant effect on the ability to detect fraud ; Professionalism, audit experience, and audit independence together have a significant influence on the ability to detect fraud. Keywords: Profession, Experience, Independence, Ability of Internal Auditors, Fraud JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8602